Diagnóstico Termoeconômico de uma Central de Cogeração do Setor Siderúrgico Utilizando o Modelo H&S - Secchin, Tarley Rezende (2015)
The Diagnosis is the analysis that allows to discover and understand signals of malfunction and quantify its effects. In Thermoeconomic Diagnosis, the effect of malfunction is quantified in terms of additional resources consumed in order to get the same production in both quality and quantity. This works aims to make a Thermoeconomic Diagnosis of a cogeneration plant inside a Steel Plant using the H&S model. Additionally, the results obtained using the H&S model are compared with the results obtained with the use of models E and E&S to verify the advantages in applying the H&S model in the development of Thermoeconomic Diagnosis. It’s a cogeneration plant operating on rankine cycle, with three closed feed water heaters and one open feed water heater, whose function is to attend the demands of mechanical energy (compressed air), electrical and thermal energy (process steam). The Thermoeconomic Diagnosis of the thermal system of this work was applied using H&S model in order to determine the anomalies in the system’s components and the contribution of every equipment in additional input consumption. The results were analyzed considering general aspects of Thermodynamics, Thermoeconomy and cogeneration that allowed calculating the efficiencies, exergy destruction in equipment and performance indicators of the plant. The Thermoeconomic model used hadn’t been applied in Thermoeconomic Diagnosis in real plants with more complexity, hence this paper presents the methodology and analysis of this models application in Thermoeconomic Diagnosis.